Effects of plyometric versus concentric and eccentric conditioning contractions on upper-body postactivation potentiation - Ulrich, Gert; Parstorfer, Mario (International journal of sports physiology and performance, 2017)
Purpose: There are limited data on postactivation potentiation’s (PAP) effects after plyometric conditioning contractions (CCs), especially in the upper body. This study compared plyometric CCs with concentric-eccentric and eccentric CCs aiming to improve upper-body power performance due to a PAP effect. Methods: Sixteen resistance-trained males completed 3 experimental trials in a randomized order that comprised either a plyometric (PLY), a concentric-eccentric (CON), or an eccentric-only (ECC) CC. Maximal muscle performance, as determined by a ballistic bench-press throw, was measured before (baseline) and 1, 4, 8, 12, and 16 min after each CC. Results: Compared with baseline, bench-press power was significantly enhanced only in CON (P = .046, ES = 0.21) after 8 min of recovery. However, the results obtained from the comparisons between baseline power performance and the individual best power performance for each subject after each CC stimulus showed significant increases in PLY (P < .001, ES = 0.31) and CON (P < .001, ES = 0.38). There was no significant improvement in ECC (P = .106, ES = 0.11). Conclusions: The results indicate that only CON CCs generated increases in bench-press power after 8 min of rest. However, considering an individual rest interval, PLY CCs led to an enhanced power performance in the bench-press exercise, and this increase was comparable to that induced by CON CCs. Due to the easy practical application before a competition, PLY CCs might be an interesting part of warm-up strategies aiming to improve upper-body power performance by reason of PAP.